An Assessment of the audit trail in pension management information systems :a case study of the pension department - Mboni, Alphaxard Kyalo (Strathmore University, 2012)
The purpose of this study was to assess the existing Audit Trail Model of the Pension Management Information System (PMIS), in the Pensions Department of the Ministry of Finance, Kenya, to track the processing of pension claims. The study assessed the weakness of existing Audit Trail model in use, identify and propose Audit Trail model that will address the needs of PM IS and identify ways of improving the use of Audit Trail. The study was a purposive targeting the key informants; Pension Directors, PMIS Administrators, Pension Accountants, and Pension Clerks dealing with the PMIS in various units. The Retirees were reached through snow ball technique. Both quantitative and qualitative data collection techniques were used; secondary data collection was also used through existing newsletters, office memos, text books and journals. Quantitative data from questionnaires was analyzed and interpreted with the help of the Statistical Package for the Social Sciences (SPSS). Qualitative analysis was undertaken through summarizing, categorization and structuring of meaning by drawing relationships in the study results of the Audit Trail model. The study found that the Audit Trail in the PMIS does not keep a chronological record of events; information captured is scanty and can not help Pensions Directors make informed decisions. Further, the study found that the purpose of the Audit Trail in the PMIS as used by the Pension Management is only for security reasons and tracking the whereabouts of a particular file. On the basis of information gathered during the research a more appropriate Audit Trail Model is proposed. The research also provided a foundation for future research on the Audit Trail in Pension Systems of developing countries and on Pension Systems policies. The conclusions and recommendations on the model of Audit Trail provide the Government, development partners, consultants, retirees and other stakeholders with a clear idea of the contribution it can make, and how it can assist in prioritization, planning of resource allocation in the Pension Department and toward realizing vision 2030.
Partial fulfillment of the award of Master of Science in Computer-based information systems (MSIS)
Keywords: Database security